2009
DOI: 10.1021/jp903965d
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Arrays of Gold Nanodisks for Plasmon-Mediated Brillouin Light Scattering

Abstract: Distributions of electric fields in two-dimensional arrays of gold nanodisks on a Si 3 N 4 membrane, with light incident through the membrane, are modeled with the aim of determining array geometries for effective plasmon-mediated Brillouin light scattering ("surface-enhanced Brillouin scattering") from phonons or magnons in a specimen placed in contact with such an array. Particular attention is devoted to average intensities and higher-wavevector components of the fields in a plane 2 nm from the circular nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…For near-field interaction with the gap width between plasmonic nanoparticles >10 nm, typically only moderate enhancement occurs. For instance, | E | 2 /| E 0 | 2 ∼10 was reported for dense rectangular square arrays of gold disk nanoparticles [ 46 , 47 ] at wavelengths of 530–630 nm. Similarly, an inverse structure of densely packed nondiffractive arrays of nanoholes yields intensity enhancements of | E | 2 /| E 0 | 2 ∼16 at wavelength of λ = 600 nm [ 46 ].…”
Section: Surface Plasmon Field Intensity Enhancementmentioning
confidence: 99%
“…For near-field interaction with the gap width between plasmonic nanoparticles >10 nm, typically only moderate enhancement occurs. For instance, | E | 2 /| E 0 | 2 ∼10 was reported for dense rectangular square arrays of gold disk nanoparticles [ 46 , 47 ] at wavelengths of 530–630 nm. Similarly, an inverse structure of densely packed nondiffractive arrays of nanoholes yields intensity enhancements of | E | 2 /| E 0 | 2 ∼16 at wavelength of λ = 600 nm [ 46 ].…”
Section: Surface Plasmon Field Intensity Enhancementmentioning
confidence: 99%
“…Recently, many studies have been focused in the optical properties of non-spherical metal nanoparticle arrays, such as nanorods [27], nanodisks [28], nanowires [29]. Yin et al reported the SPR peak shift of a one-dimensional silver cylinder array with different interparticle distances [30].…”
Section: Introductionmentioning
confidence: 99%
“…enhancement in δ R (∼120) is observed (and also in δ R/R, ∼70) compared to that of the pillar (that appears to be non-resonant at this frequency). Excluding the void-centre vibrationalresonance enhancement factor of Q ≈ 20 for this mode (see table 1), this suggests a factor ∼6 enhancement in δ R. Plasmon-mediated signal enhancements are observed in SERS [44][45][46][47][48], and related enhancements in the case of coherent acoustic phonons can be termed surfaceenhanced stimulated Brillouin scattering (SESBS) by analogy to the non-stimulated version SEBS (for which thermally-excited incoherent phonons provide the scattering source) [49,50]. By analogy with SERS or SEBS, the enhancement in SESBS depends on the plasmon-enhanced optical amplitudes at the pump and probe wavelengths.…”
Section: Ultrafast Imagingmentioning
confidence: 99%